Role of CT Scan in Diagnosis and Management of Otogenic Intracranial Abscess - Prashanth, V. (Springer-Verlag, 2011)
The existence of complications of suppurative otitis media and efforts to control it go far back into history. Early diagnosis and management have been greatly modified by the extensive use of CT scan and higher antibiotics. Despite an overall decline in the incidence of complications of otitis media, severe complications still exist with high mortality. Suggested reasons are decrease in physician’s experience and changing of the virulence and susceptibility of causative organism. This series is a prospective study of 18 cases of otogenic brain abscess, carried out in Department of ENT and Head & Neck Surgery, SSG Hospital, Baroda from June 2005 to June 2008. We emphasize on confirmation of resolution of brain abscess by CT scan. This will eliminate recurrent/residual abscess and help in reduced overall mortality and morbidity.